Spatially Resolved Sensitivity of Single-Particle Plasmon Sensors - Beuwer, Michael A. (J Phys Chem C Nanomater Interfaces, 2018)
[Image: see text] The high sensitivity of localized surface plasmon resonance sensors to the local refractive index allows for the detection of single-molecule binding events. Though binding events of single objects can be detected by their induced plasmon shift, the broad distribution of observed shifts remains poorly understood. Here, we perform a single-particle study wherein single nanospheres bind to a gold nanorod, and relate the observed plasmon shift to the binding location using correlative microscopy. To achieve this we combine atomic force microscopy to determine the binding location, and single-particle spectroscopy to determine the corresponding plasmon shift. As expected, we find a larger plasmon shift for nanospheres binding at the tip of a rod compared to its sides, in good agreement with numerical calculations. However, we also find a broad distribution of shifts even for spheres that were bound at a similar location to the nanorod. Our correlative approach allows us to disentangle effects of nanoparticle dimensions and binding location, and by comparison to numerical calculations we find that the biggest contributor to this observed spread is the dispersion in nanosphere diameter. These experiments provide insight into the spatial sensitivity and signal-heterogeneity of single-particle plasmon sensors and provides a framework for signal interpretation in sensing applications.